Culturally Safe Neonatal Care: Talking With Health Practitioners Identified as Champions by Indigenous Families. (May 2023) - Adcock, Anna; Cram, Fiona; Edmonds, Liza; Lawton, Beverley
The burden of health inequities borne by Indigenous peoples can be overwhelming, especially when mothers and newborns' lives are at stake and health services seem slow to invest in responsiveness. In Aotearoa (New Zealand), urgent action is required to eliminate persistent systemic inequities for Māori (Indigenous) whānau (family collectives that extend beyond the household). This Kaupapa Māori (by Māori, for Māori) qualitative study aimed to explore the views of health practitioners identified as champions by whānau of preterm Māori infants. Ten health practitioners were interviewed and asked about their involvement with the whānau, their role in explanations and communication, and their thoughts on whānau coping. Interview data were analysed using interpretative phenomenological analysis. Three superordinate themes were identified: working together in partnership, a problem shared is a problem halved, and sacred space. Collaboration between health practitioners and with whānau was important to the champions and central to their goal of enabling whānau autonomy. This was built on a foundation of connectivity, relationships, and a full appreciation that childbirth is a sacred time that is potentially disrupted when an infant is born prematurely. The values- and relationship-based practices of these champions protected and uplifted whānau. They showed that health practitioners have important roles in both the elimination of inequities and the sustaining of Māori self-determination. This championship is an exemplar of what culturally safe care looks like in day-to-day practice with Māori and is a standard that other health practitioners should be held to.